PENGARUH METODE DISCOVERY LERNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIII SMPN 3 MERANGIN - Rini Widarti (Mat-Edukasia, 2019)
This study aims to describe the ability to solve mathematical problems using the Discovery Learning method better than conventional learning in the form of algebraic material for class VIII students of SMPN 3 Merangin. Sampling using simple random sampling technique. The selected sample is class VIIIC as an experimental class and class VIIID as a control class. Data collection techniques through tests of mathematical problemsolving ability in the form of essay questions on Algebra material. The data analysis technique used to test hypotheses is the t-test. From the analysis of the final test data in the experimental class obtained an average of 50.25 while the control class obtained an average of 34.248. Hypothesis test results obtained, = 7.260 and = 1.685. Because> then H0 is rejected and H1 is accepted. The conclusion of this research is the mathematical problemsolving ability of students of class VIII SMP N 3 Merangin using Discovery Learning Method is better than students' mathematical problemsolving abilities taught by Conventional Learning.